Recent Advances on the Understanding of Structural and Composition Evolution of LMR Cathodes for Li-ion Batteries - Yan, Pengfei; Zheng, Jianming; Xiao, Jie; Wang, Chong-Min; Zhang, Ji-Guang (Frontiers in Energy Research, 2015)
Lithium-rich, magnesium-rich (LMR) cathode materials have been regarded as very promising for lithium (Li-ion battery applications. However, their practical application is still limited by several barriers such as their limited electrochemical stability and rate capability. In this work, we present recent progress on the understanding of structural and compositional evolution of LMR cathode materials, with an emphasis being placed on the correlation between structural/chemical evolution and electrochemical properties. In particular, using Li[Li0.2Ni0.2Mn0.6]O2 as a typical example, we clearly illustrate the structural characteristics of pristine materials and their dependence on the material-processing history, cycling-induced structural degradation/chemical partition, and their correlation with electrochemical performance degradation. The fundamental understanding that resulted from this work may also guide the design and preparation of new cathode materials based on the ternary system of transitional metal oxides.